Characteristics of Algebraic Problem Solving Based on Learning Styles in PISA Content-Type Questions Change and Relationship - Anita Maharani; Samijo Samijo; Bambang Agus Sulistyono (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study aims to describe the characteristics of algebraic problem solving based on students' learning styles on PISA content type questions change and the study used a descriptive qualitative approach with a population of students at SMA Negeri 1 Kediri. Subjects were selected using a learning style questionnaire, resulting in three research subjects, each representing visual, auditory, and kinesthetic learning styles. The research instruments included a learning style questionnaire, PISA-type content questions, and a questionnaire change and relationship Level 4 with a moderate level of difficulty, along with interview guidelines. The analysis of problem-solving characteristics is based on Polya's problem-solving indicators: understanding the problem, planning a solution, implementing the plan, and reexamining the solution. The results showed that subjects with a kinesthetic learning style were able to complete all stages of problem-solving and achieved the highest score compared to other learning styles. These findings also indicate that PISA content-type questions change, and relationships reveal the characteristics of students' algebraic problem solving based on learning styles.